De teloorgang van het poldermodel: Een verhaal van winnaars en verliezers - Soens, Tim (TSEG - The Low Countries Journal of Social and Economic History, 2023)
The myth was that, If there is one field in which the polder model prevailed, it would have to be the water management. Yet even there the historiography is evolving in the opposite direction: already in the 2000s, it was demonstrated that many polders and water boards were by no means paragons of consultation and participation, and that, if such participation existed, it declined considerably in importance from the late Middle Ages onwards. Just as society was unequal, participation in water management was unequal. Translated with DeepL